Delirium, dementia and depression - Boland, Michael; Traynor, Rosie; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2010)
Delirium and dementia are two of the most common mental disorders elderly people face. Depression is also common in elderly people and often presents with symptoms similar to dementia or delirium. The differentiation between these three conditions can be difficult because many symptoms overlap. As the cause of so much suffering and discomfit, it is important these conditions are effectively addressed by medical staff. This program defines these conditions by detailing symptoms and speaking to medical experts. Potential risk factors, causes of delirium and assessment criteria for all three conditions are outlined along with a brief summary of management strategies. [Container].
Introduction -- Definitions -- Assessment -- Differentiation -- Delirium: risk factors and causes -- Treatment -- Conclusion.
All regions DVD.
Writer/Director, Michael Boland.
Voice over: Rosie Traynor.
Keywords: Delirium; Dementia -- Patients; Depressed persons